Omega-3 long chain highly unsaturated fatty acid content in tissue correlates with escape response efficiency in golden gray mullet - Vagner, Marie; Ducos, Salomé; Graziano, Nicolas; Le Grand, Fabienne; Bideau, Antoine; Dubillot, Emmanuel; Lefrançois, Christel (Frontiers in Fish Science, 2024)
Omega-3 long-chain highly unsaturated fatty acids (n-3 HUFA) are poorly synthesised de novo by marine fish, but are necessary to maintain their metabolic and physiological performance. Consequently, fish must find them in their diet. However, the availability of these lipid compounds is predicted to decrease in relation to global changes in ocean waters. The aim of this study was to experimentally determine the effects of an n-3 HUFA-deficient diet on the escape performance of Chelon auratus, a microphytobenthos grazer of high ecological importance. Fish were fed either a standard n-3 HUFA diet or an n-3 HUFA-deficient diet for two months. At the end of this conditioning period, several variables (latency, responsiveness, initial direction of escape, response duration, distance covered, maximum acceleration and velocity, turning rate) related to escape performance were characterised in the tested fish. The results showed that a lower dietary n-3 HUFA content caused a significant reduction in the proportion of these fatty acids in fish muscle, both in membranes and in reserves. While the FA composition of the brain also reflected that of the diet in reserves, the membrane fatty acid composition of the brain remained similar between the two dietary groups, suggesting the preservation of neural and cognitive functions of the fish. Neither growth rate nor escape response variables were significantly different between the two diets. However, some escape response variables (e.g. latency, duration, maximum velocity and acceleration, turning rate) were highly correlated with fish n-3 HUFA content in brain or muscle, and these correlations were tissue specific. While response duration and latency seemed to be more correlated with n-3 HUFA content in the brain membrane, other escape response variables such as turning rate, maximum velocity, cumulative distance and maximum acceleration seemed to be correlated with n-3 HUFA content in the lipid reserve, both in the brain and in the muscle. Our results indicate that the reduction of n-3 HUFA in the dietary sources of marine fish appears to reduce the performance of the escape response, suggesting some impact of n-3 HUFA dietary changes with global change on predator-prey relationships within the marine ecosystem.